Unravelling taboos and cultural beliefs associated with hidden hunger among pregnant and breast-feeding women in Buyende district Eastern Uganda - Patience Tugume; Abubakar Sadik Mustafa; Abdul Walusansa; Samuel Ojelel; Evelyne B. Nyachwo; Emmanuel Muhumuza; Maria Nampeera; Fredrick Kabbale; Jamilu.E. Ssenku (BMC, 2024)
Abstract Background Food taboos and cultural beliefs among pregnant and breast-feeding women influence their food consumption patterns and hence the health of women and unborn children. Cognizant of their neglect in programs aimed to ameliorate hidden hunger among pregnant and breast-feeding women in Buyende and other resource-poor communities in sub-Saharan Africa, we opted for a study to unravel them to inform program design. Methods We documented food taboos and beliefs amongst pregnant and breast-feeding women from six sub-counties of Buyende district in Eastern Uganda. A mixed-methods approach was used, which was comprised of questionnaire interviews with 462 women, eight focus group discussions with 6-10 participants in each and a total of 15 key informant interviews. Results The present study revealed that 129 (27.9%) of the respondents practice food taboos and adhere to cultural beliefs related to their dietary habits during pregnancy and breast-feeding that are fuelling the prevalence of hidden hunger. The most tabooed foods during pregnancy were sugarcane (17.8%), fishes which included lung fish, catfish and the Lake Victoria sardine (Rastrineobola argentea) (15.2%), oranges (6.6%), pineapples (5.9%), eggs (3.3%), chicken (3.3%) and cassava, mangoes and Cleome gynandra (each at 3%). Most foods were avoided for reasons associated with pregnancy and labour complications and undesirable effects on the baby. Most women learnt of the taboos and beliefs from the elders, their own mother, grandparents or mother-in-law, but there was also knowledge transmission in social groups within the community. Conclusions The taboos and cultural beliefs in the study area render pregnant and breast-feeding women prone to micronutrient deficiency since they are denied consumption of a diversity of nutritious foods. There is a need to educate such women about consumption of nutrient-rich foods like fish, eggs, fruits and vegetables in order to improve their health, that of the unborn and children being breast fed. Additionally, culturally appropriate nutrition education may be a good strategy to eliminate inappropriate food taboos and beliefs with negative impact on the health of pregnant and breast-feeding women.